Utilising GPS data to quantify torso range of motion in field hockey athletes - Warman, G. E.; Chalkley, D.; Cole, M. H.; Pepping, G.-J. (Proceedings, 2018)
Global Positioning System (GPS) along with micro-electrical mechanical system (MEMS), technology is now commonplace in today`s sporting environment. Little has been published utilising this combination of technologies to quantify the postures of athletes during match-play. This paper presents the results of a preliminary investigation into developing a methodology that allows practitioners to use the technology readily available to them to quantify the postural demands of field hockey players during match-play.